The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1073/pnas.011417098
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence for the participation of gap junction-mediated intercellular communication in the transmission of damage signals from alpha -particle irradiated to nonirradiated cells

Abstract: It has generally been considered that important biological effects of ionizing radiation arise as a direct consequence of DNA damage occurring in irradiated cells. We have examined this hypothesis by exposing cells to very low fluences of ␣-particles, similar to those emitted by radon gas, such that as few as 1% of the cells in a population are traversed by a particle and thus receive any radiation exposure. By using the endpoints of changes in gene expression and induction of DNA damage, we show that nonirrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
297
1
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 422 publications
(305 citation statements)
references
References 22 publications
6
297
1
1
Order By: Relevance
“…Those studies were performed with cells at low densities where cell-to-cell contact was minimal and therefore a media-related factor was involved. However, other studies in confluent monolayers of fibroblasts showed that GJIC also played a role in propagation of the bystander effect (Azzam et al, 1998(Azzam et al, , 2001). Urothelium has highly developed connexin-mediated intercellular communication (Grossman et al, 1994;Lyng et al, 1996) and this could explain the more pronounced bystander effect observed in the urothelial outgrowth in comparison with fibroblast cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those studies were performed with cells at low densities where cell-to-cell contact was minimal and therefore a media-related factor was involved. However, other studies in confluent monolayers of fibroblasts showed that GJIC also played a role in propagation of the bystander effect (Azzam et al, 1998(Azzam et al, , 2001). Urothelium has highly developed connexin-mediated intercellular communication (Grossman et al, 1994;Lyng et al, 1996) and this could explain the more pronounced bystander effect observed in the urothelial outgrowth in comparison with fibroblast cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (Azzam et al, 1998(Azzam et al, , 2001) have demonstrated that the bystander effect is dependent on gap junction intercellular communication (GJIC) in confluent cultures of primary human diploid fibroblasts exposed to low fluences of a-particles. These showed that p53 and p21 mediated pathways are activated (Azzam et al, 2000).…”
mentioning
confidence: 99%
“…However, the mechanisms involved in bystander signalling have only partially been elucidated and are probably dependent on cell type and end points investigated. The involvement of soluble factors like reactive oxygen species (ROS) (Azzam et al, 2002;Shao et al, 2003aShao et al, , 2005, nitric oxide (NO) (Shao et al, 2003b(Shao et al, , 2005Sokolov et al, 2005) and cytokines released from irradiated cells as well as gap junction intercellular communication (Azzam et al, 2001;Shao et al, 2003a;Mitchell et al, 2004;Sokolov et al, 2005) have recently been reported. Most interestingly, several cytokines can be induced by ROS and NO/NOS (Ayache et al, 2002;Hsu and Wen, 2002;Kosmidou et al, 2002;Hwang et al, 2004;Ryan et al, 2004) providing a possible link between different factors potentially involved in bystander signalling.…”
Section: Introductionmentioning
confidence: 99%
“…The culture medium was replaced every 2 days and the cells were irradiated at day 3 under full confluent condition. At that time, about 92% of the cells were in G0-G1 as determined by flow cytometry (Azzam et al, 2001). …”
Section: Methodsmentioning
confidence: 99%